Epidemiological study of goats infected with diarrhia caused by some bacteria of enterobacteriaceae: AL-Darraji,A.J.Z and yousif, A.A - J.Z, AL-Darraji A. (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted to isolate of Enterobacteriace family and designed to determine the prevalence of this bacteria in goats in 6 residance area in Baghdad Governorate ( Yousifia, Mahmodia, Shoulla, Sader city, Khadmia and farm of College of Veterinary Medicine ). 300 fecal samples were collacted from diarrheaic goats aged between (1 day to 2 year) from male and female for many month ,Diagnostic study depending upon the morphological and cultural properties of the isolates on some selective media in addItion to different biochemical tests and API-20E and serological tests isolates of Salmonella. The results showed Isolation of 111bacterial Isolates which included 6 different species of enterobacteriace, Citrobacte braackii )48)isolates, Protues mirabilis(36) isolates, Protues vulgaris ( 4 ) isolates , Enterobacter cloacae (14)isolates , Klebsiella pneumonia isolates ( 5 ) , Salmonella enteritidis (2) isolates , Salmonella Newport(1)isolate and Providenica rettgeri(1)isolate. Results showed significant difference at p<0.05 in distribution of infection according to age of animals and months of year and didn’t showed significant difference at p<0.05 to all of bacteria isolated. In Salmonella infection the animals suffered from increase body temperature, pulse and respiratory rates, diarrhea and sever dehydration, the feces was white to green in colour containing blood , while the animals infected with other bacteria suffering from similar sings but less in severity than occurred in Salmonella.